Remembranzas de la Jornada Científica "Dra. Ana Larralde" In Memoriam - James Pita, Alberto; Morales Navarro, Denia (Revista Cubana de Estomatología, 2013)
The Cuban Society of Maxillofacial Surgery convened, under the consent of the Council of Scientific Societies of Health, the "Dr. Ana Larralde" In Memoriam Scientific Conference, in homage to this illustrious woman, the first Cuban maxillofacial surgeon, and to all the women of our specialty for the proximity of the celebration of "Mother's Day". This day was the result of the continuity of the work aimed at constant scientific communication among our professionals, carried out by the current governing body of the society, and whose important background was the development of the quarterly scientific meetings and the International Stomatology Convention 2010, of which we were part of the organizing committee. Based on the fulfillment of the work objectives, outlined by the current Governing Board, to revitalize the Cuban Society of Maxillofacial Surgery and develop a program of scientific activities that contributes to the continued improvement of our membership, all efforts were focused on the celebration, at the headquarters of the Council of Scientific Societies of Health, on May 3 and 4, 2012 of the "Dra. Ana Larralde" In Memoriam Day.